SIKAP MAHASISWA JURUSAN PENDIDIKAN LUAR BIASA FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI JAKARTA TERHADAP PENINGKATAN KETERAMPILAN SOSIALISASI ANAK TUNA GRAHITA MELALUI PENDIDIKAN INKLUSIF - Siti Nuraini (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2008)
The purpose of this research is to discover the attitude of the students of special education program at School of Education, State University of Jakarta towards the development of social skills of the students with intellectual skills through inclusive education. This research conducted in the academic year of 2006/2007 used closed questionnaire with Likert Scale, for the sample 30 students were selected purposively. The findings show that the students’ attitude in ranged between positive and negative.